Memories of Hardwick Hall ... - Project Team, Their Finest Hour (University of Oxford, 2024)
Evelyn and Harry met in Derbyshire in Hardwick Hall, Chesterfield during the war.Evelyn was born in Derby in 1920. Henry was born in Preston, Lancashire, in 1919.They met in Chesterfield because the parachute regiment was based in Hardwick Hall. Henry joined the parachute regiment in 1943. He had signed up for the war in 1939 at the age of 19 years.The 'individual report for Harry Leeming' records reports of his military service in various locations including Dunkirk, France (1940), and Faroes (1942-43). On his return from Faroes, he joined the parachute regiment in 1943. Among his medals for service issued by British Government are the 1939-43 Star, and the 1945 France and Germany Star. At the end of the war in 1946, he was discharged as unfit for service because of disablement from wounds. He applied for assessment to no effect- because pension payments depend on the degree of assessed disability. He got wounded at some of the main points of the war, for example, in Dunkirk on D-Day. He was in the ...